On deferred statistical convergence in fuzzy normed linear spaces - Shyamal Debnath; Santonu Debnath (Journal of Fuzzy Extension and Applications)
In this paper, we introduce the notions of deferred statistically convergent sequence and deferred statistically Cauchy sequence in a fuzzy normed linear space(FNS) and establish some basic facts. We also define deferred statistical limit points and deferred statistical cluster points of a sequence in FNS and investigate the relations between these concepts.